Field Experience Report in Public Health Nutrition - Brenes, Priscilla (My University, 2017)
This field experience objective was to provide public health experience outside academia in order to apply the skills and knowledge acquired during the public health courses as well as emphasis courses. Meadowlark Hills (MLH) Retirement Community, a not-for-profit organization located in Manhattan, Kansas, served as the agency to complete my field experience. MLH has an innovative senior living approach that embraces a person-centered philosophy. The specific objectives of this field experience were to integrate public health nutrition knowledge in a practice setting; experience organizational structure, program administration, coordination, and community relationships; create nutrition education handouts for residents and staff of MLH; and demonstrate creativity and teamwork in the development of public health activities. This field experience consisted of nine weeks of rotations in the following departments: administration, home health, finance, social work, resident services (transportation), Parkinson's program, memory program, and dietetics. My main project at MLH was to develop educational materials for staff and residents about hydration, constipation, bone health, and possible dietary protein-drug interactions.
Keywords: Public Health Nutrition; Nutrition Education; Older Adults